Anticoccidial Activity of Aloe debrana and Aloe pulcherrima Leaf Gel against Eimeria Oocysts - Andualem Yimer Desalegn; Mulubrihan Rahimeto Ahmed (Journal of Parasitology Research)
Avian coccidiosis is one of the serious infectious diseases that pose huge impact on the health and production of poultry, hence mainly controlled by regular use of prophylactic and therapeutic chemical drugs. Frequent use of anticoccidial drugs, however, has resulted in the development of resistance in the Eimeria species and concerns about drug residues which have stimulated the efforts to search for alternative. Aloe pulcherrima and Aloe debrana are some of the endemic Aloe species of Ethiopia which are traditionally used for the treatment of various infectious diseases. In this study, an in vitro trial was undertaken to evaluate the effect of Aloe debrana and A. pulcherrima leaf gel infusions on the inhibition of the sporulation of oocysts of mixed Eimeria species isolated from naturally infected chickens. In this assay, petri dishes containing unsporulated coccidian oocysts at a dose of 1500 oocysts/ml of fecal solution were randomly assigned to 10, 15, 25, and 30% w/v crude gel infusion of both aloe species in 1% potassium dichromate solution while Amprolium and distilled water served as control groups. The results of this study show that 10, 15, 25, and 3 0% w/v gel infusions at the tested concentrations have anticoccidial activity as evidenced by their ability to decrease significantly (P<0.05) the sporulation of Eimeria oocysts relative to the control incubation. The efficacy of A. debrana was found significantly better (P<0.05) than A. pulcherrima at different concentrations. However, A. debrana at 30% concentration showed significantly higher (P<0.05) sporulation inhibition efficacy of 79.35% (CI: 75.99-83.21) compared to A. pulcherrima (69.17%, CI: 64.65-73.92) at similar concentration in relation to the control incubation, though this could not be compared to Amprolium which was more effective (P<0.05) with an inhibition percentage of 90.54% (CI: 89.16-92.21). This study has shown that there is potential for use of Aloe debrana leaf gel for the control of avian coccidiosis and as a chemotherapeutic, though much research is needed to determine absolute concentration which will make it comparable to commercially available drugs in terms of efficacy.